Investigating the learner's performance in learning programming by integrating visualization programming and pair programming in programming courses / Nurul Aini Sairuni - Sairuni, Nurul Aini (2015)
This paper investigates the possible learning approach for novices in learning programming. Novices have problem in learning programming because many reasons. One of it is the incorrect use of study methodology. Many approaches have been introduce, however, there are no empirical evidence showing the best approach to learn programming by novices. In this study, four experiments were conducted with four groups of students for four different learning approaches, that are the conventional method for Group A, pair programming for Group B, using the visualization programming tool for Group C and combination used of visualization programming tool and pair programming for Group D. The visualization programming tool used is Ville. Each group consists of 30 students of mixed gender. The students were grouped randomly except when doing pairing which requires the pair to have different capability which is determined by their CGPA and SPM Mathematics' results. Each group will be given the pre-test, treatment and post-test. Pre test were carried out by all groups using the conventional method, while post-test were performed according to the different methods for each group. The differences in score for pre and post-test were analyzed for each experiment. The result showed that Group Dshowed a significance improvement in score as compared to other groups. Thus, it gives an indicator that teaching of programming for novices is best performed by combining the pair programming and using the visualization tools. The combination of the two techniques has improved the performance of the students